Workshop Penyusunan Perangkat Pembelajaran Berbasis Digital Untuk Pengoptimalan Pembelajaran Online pada Guru SMA Muhammadiyah Kota Kediri - Nurfahrudianto, Aan; Puji Permana Aji, Mahendra; Ratnawati, Vivi (Universitas Nusantara PGRI Kediri, 2022)
Electronic/digital-based learning tools can be easily obtained by the presence of information technology devices. Through this information technology network, educators can use it in learning. Especially during the current covid-19 pandemic which requires learning to be carried out online (in a network). Teachers/educators need to improve their abilities and skills in making learning tools. The community service team at Universitas Nusantara PGRI Kediri, took the initiative to help teachers at SMA Muhammadiyah Kediri improve their skills through workshops. The workshop can be carried out according to plan and goes well. The mastery of the material and the results of the learning media are in the very good category. Evaluation of digital learning in online learning is more varied. This activity also received a good response, as evidenced by the questionnaire given by the service team, which was included in the very good category.